High temperature oxidation of Mg2(Si-Sn). (October 2016) - Skomedal, Gunstein; Burkov, Alexander; Samunin, Alexander; Haugsrud, Reidar; Middleton, Hugh
Highlights: ⿢ The breakaway oxidation behavior of Mg2 Si1-x Snx at temperatures above 400 °C were studied. ⿢ The ignition temperature for break-away oxidation is lower for higher Sn content. ⿢ Below ignition temperature, a thin layer of MgO protects from further oxidation. ⿢ Formation of liquid Sn below the MgO layer is the main factor causing ignition. Abstract: High temperature oxidation of Mg2 Si1- x Sn x alloys ( x = 0.1 ⿿ 0.6) has been investigated. The oxidation rate was slow for temperatures below 430 °C. In the temperature range between 430⿿500 °C all the alloys exhibited breakaway oxidation. The onset temperature of the breakaway region in general decreased with increasing level of Sn in the alloy. The breakaway behavior is explained by a combination of the formation of a non-protective MgO layer and the formation of Sn-rich liquid at the interface between the oxide and Mg depleted Mg2 Sn.